Conformational Heterogeneity and the Affinity of Substrate Molecular Recognition by Cytochrome P450cam - Basom, Edward J. (Biochemistry, 2017)
The broad and variable substrate specificity of cytochrome P450 enzymes makes them a model system for studying the determinants of protein molecular recognition. The archetypal cytochrome P450cam (P450cam) is a relatively specific P450, a feature once attributed to the high rigidity of its active site. However, increasingly studies have provided evidence of the importance of conformational changes to P450cam activity. Here we used infrared (IR) spectroscopy to investigate the molecular recognition of P450cam. Toward this goal, and to assess the influence of a hydrogen bond (H-bond) between active site residue Y96 and substrates, two variants in which Y96 is replaced by a cyanophenyl (Y96CNF) or phenyl (Y96F) group were characterized in complexes with the substrates camphor, isoborneol, and camphane. These combinations allow for a comparison of complexes in which the moieties on both the protein and substrate can serve as a H-bond donor, acceptor, or neither. The IR spectra of heme-bound CO and the site-specifically incorporated CN of Y96CNF were analyzed to characterize the number and nature of environments in each protein, both in the free and bound states. Although the IR spectra do not support the idea that protein–substrate H-bonding is central to P450cam recognition, the data altogether suggest that the differing conformational heterogeneity in the active site of the P450cam variants and changes in heterogeneity upon binding of different substrates likely contribute to their variable affinities via a conformational selection mechanism. This study further extends our understanding of the molecular recognition of archetypal P450cam and demonstrates the application of IR spectroscopy combined with selective protein modification to delineate protein–ligand interactions.